The Development of a Digital-Based Educational Quality Ecosystem at SMK Bhineka Karawang - Wahyudin, Undang; Nurlailasari, Ella; Permana, Hinggil; Irwansyah, Ridwan (Yayasan Sinergi Kawula Muda, 2025)
This study analyzes the development of a digital-based educational quality ecosystem at SMK Bhineka Karawang, Indonesia, focusing on enabling factors, challenges, and strategies to sustain digital transformation in vocational education. The research is driven by the urgency of educational digitalization in the industry 4.0 era, which demands the integration of leadership, teacher competence, infrastructure, policies, and school culture. A qualitative case study design was applied through in-depth interviews with eight informants (the principal, vocational teachers, and IT staff) selected purposively, supported by document analysis, and examined using thematic analysis. The findings highlight three key themes with measurable indicators: (1) leadership commitment and policy alignment, evident in digital planning documents and resource allocation; (2) teacher digital competence and continuous professional development, reflected in participation rates in digital training; and (3) infrastructure readiness and integration challenges, measured by facility availability and system interoperability. The results indicate that the success of a digital ecosystem requires a systemic approach that combines leadership vision, teacher empowerment, and well-coordinated infrastructure support. This study enriches the limited literature on digital transformation in Indonesian vocational schools by presenting an empirically grounded framework. It offers guidelines for practice, including leadership training in digital change management, differentiated teacher development programs, and sustainable infrastructure planning aligned with pedagogical goals.